PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN MODEL PEMBELAJARAN MIND MAPPING DI SEKOLAH DASAR - Surwani, Surwani; Halidjah, Siti; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem, whether the use of learning model to mind mapping can improve the writing skill of narrative on students of grade V SDN 03 Pontianak City.This research aimed to improve students' writing skill of narrative learning model to mind mapping students of grade V SDN 03 Pontianak City. The method used is descriptive method with class action research form. This study was conducted during III cycle with cycle two time meeting in cycle I and one time meeting in cycle II and III . The results of the study design of the learning (RPP) of the cycle I is 3,05, the cycle II is 3,54 and, the cycle III is 3,84. The results of research from the implementation of learning from the cycle I is 3,01, the Â cycle II is 3,40, and the cycle III is 3,60. The result of research writing of narrative essay from cycle I that is 8,57, cycle II that is 9,14, and cycle III that is 10,15. So applying of learning model to mind mapping can improve writing narrative skill students.Â Keywords: Writing Skills of Narrative, Â Mind Mapping